Insulating a WTO Investment Facilitation Framework from ISDS - George A. Bermann; N. Jansen Calamita; Manjiao Chi; Karl P. Sauvant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
The authors identify several ways in which an investment facilitation framework for development can be insulated from investor-state dispute settlement provisions in international investment agreements, and suggest specific formulations in this respect.
Keywords: 330